Effect of age and weight on physical activity - Rivan Virlando Suryadinata; Bambang Wirjatmadi; Merryana Adriani; Amelia Lorensia (SAGE Publishing, 2020)
Background: Individuals tend to develop metabolic disorders and other chronic diseases, due to the poor conduction of physical activities. Meanwhile, a high level of physical activity positively affects the quality of life. However, irrespective of the numerous studies reported on the correlation between age, weight, and physical activity, there is limited study on the differences of physical activities in the geriatric and adult groups of obese and non-obese people. This study, therefore, aims to investigate the effect of age and weight on physical activity in geriatric and adult groups. Design and methods: The purposive sampling technique was used to obtain data from 154 respondents from community-integrated health care in Surabaya, East Java, Indonesia. These respondents were equally divided into two groups of adult (21-60 years) and geriatric (>60 years) groups. Results: The Chi-Square test showed that there were no significant differences between physical activity in the obese and nonobese people of the geriatric groups (P>0.05). Conversely, in the adult group, there were significant differences between physical activities and the age of obese and non-obese groups (P<0.05). Conclusions: In conclusion, age affects physical activity in adult and geriatric groups.